ANALYSIS AND DESIGN USING BEAM CONSTRUTION OF THE PELITA BANGSA SCHOOL IN THE CIREBON CITY - Azhardi Azhardi; Arief Firmanto (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2018)
ABSTRACTThe success of the development from an area, which can be seen from the education level of the population. Increasingly developed education level of the population, it will be bring to the level of welfare for the population. Pelita Bangsa School Cirebon is a private school which has a ladder Play Group, Kindergarten, Elementary School, Junior High School and Senior High School, which is located in the city of Cirebon at the address on Terusan Laut Arafuru Street Blok A1 kavling . 6-7 Cirebon 45131 West Java.The additional building facilities of Pelita Bangsa School will be investigated in this thesis which is about structural analysis and design using steel material with LRFD (Load Resistance Factor Design) system.Analyze and design the construction of Pelita Bangsa School building with design code SNI-1729-2015 for building steel structures, SNI-1727-2013, PPPURG 1987 for loads and then SNI-1726-2012 for earthquake analysis.Analyze the structure with the help of SAP2000 (Structure Analysis Program 2000) software and design the building of Sekolah Pelita Bangsa using steel material.Keywords: Analysis and design structure, LRFD, steel material, SAP2000